ENGARUH KOLONIAL BELANDA PADA SISTEM PERTANIAN MASYARAKAT NIMBORAN - Kawer, Sonya Martha (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
The Dutch Colonial Government came to Hollandia (Jayapura) around 1946, then they made Nimboran district as a farming base, particularly on cacao and rice. In this farming system, the community of Nimboran was also provided farming tools by the Colonial Government that helped them to work. The Government also guided them to get their principle commodities and to sell their farm products. Therefore, the main focus on this research is the influence of the Colonial Government in agriculture for the Nimboran Community.